Pattern of Alleged Homicidal Deaths in and Around Cooch Behar Region - Deepmalya Sengupta 1 , Pranabesh Bharatee 2, Saikat Saha 2 , Rajib Prasad 3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Homicidal deaths are a significant public health problem and affect every society around the world. Theincidence of homicide has seen a worldwide upsurge with varying trends across geographical locations.Detailed information on the characteristics of victims of homicide from the Cooch Behar region is limited.This article explores recent trends of homicide in the Cooch Behar region. The study was conducted betweenJune 2019 to May 2020 at the Department of Forensic Medicine and Toxicology, Cooch Behar GovernmentMedical College and Hospital, Cooch Behar. 1133 autopsies were conducted over the time-period with 70homicidal deaths. Most of the victims were males (70%) with a male to female ratio of 2.33:1. 34.3% ofvictims were between the ages of 21 – 30 years. Most of the victims were laborers (18.6%) while Hinduismwas the most common religion (65.7%). 06:00 pm to 12:00 midnight was the time when the majority ofthe incidents took place and 68.5% of victims were brought dead. Injuries by hard blunt weapons andsharp cutting weapons were responsible for maximum deaths, constituting 21 (30%) and 15 (21.4%) casesrespectively. Multiple regions of the body were involved in 35.7% cases followed by head and face regionwith 34.3% cases. This study is significant as it aims to identify the profile of risk factors of victims ofhomicide and suggest new lines of research that would help to reduce the number of homicides.